Developing BTEM-Based Virtual Biology Laboratory to Improve Students' Critical Thinking Skills on the Concept of Bacteria - Ipin Aripin; Yeni Suryaningsih (Scientiae Educatia: Jurnal Pendidikan Sains, 2020)
The Covid-19 pandemic that has hit the entire world has caused changes in learning patterns from classroom to virtual classroom activities, and this has caused biology teachers to experience problems when teaching material through direct practicum activities. There is a need for solutions that can facilitate practicum activities by developing a virtual laboratory application. This research develops a Virtual Biology Laboratory (VLab-Bio) application based on Biology, Technology, Engineering, and Mathematics (BTEM) that is feasible and practical to facilitate virtual lab work on the concept of bacteria. The application product produced from this research is expected to help students facilitate practicum activities and improve critical thinking skills on the concept of bacteria. The application produced from this research is expected to help students improve their critical-thinking skills and lab work on bacterial material. Akker development model was used with four stages of development: preliminary research, prototyping, summative evaluation, and systematic reflection and documentation. The research instrument consisted of tests of critical-thinking skills and non-tests in the form of observations of the learning process and student response questionnaires. The research data were analyzed qualitatively and quantitatively with the paired t-test. The results showed that the BTEM-based virtual laboratory developed was classified as valid and effective in improving students’ critical-thinking skills with 78% effectiveness. Based on this research, it can be recommended that using a BTEM-based virtual laboratory can be used as a supplement in facilitating bacterial concept practicum activities. For further application development, it is hoped that the application can provide flexibility for students to develop their own practicum procedures in applications.